The Effectiveness of Compression Therapy in the Prevention of Venous Thromboembolic Complications in Patients With COVID-19 - R. E. Kalinin; I. A. Suchkov; A. B. Agapov; N. D. Mzhavanadze; D. A. Maksayev; A. A. Chobanyan (Неотложная медицинская помощь)
Background The main method for preventing thrombotic complications in patients with coronavirus infection is anticoagulant therapy (ACT). However, its use is not always possible, in particular in patients with bleeding. The only method of prevention in this case is elastic compression (EC) of the lower extremities.Aim of study To evaluate the effectiveness of lower extremity EC for the prevention of venous thromboembolic complications (VTEC) in patients with a new coronavirus infection.Material and methods The study was approved by the local Ethics Committee of the Ryazan State Medical University of the Ministry of Health of Russian Federation and registered on the ClinicalTrials.gov platform (identifier NCT05143567). The study included 69 patients without prophylactic compression (Group 1) and 65 patients who used prophylactic compression stockings (Group 2). The patients were treated in the covid hospital from July to November 2021. All patients had verified coronavirus infection, they took ACT and underwent ultrasound duplex scanning of the veins of the lower extremities upon admission, in the intensive care unit and upon discharge. We assessed the frequency of venous thromboembolic complications (VTEC), hemorrhagic complications, and mortality. To assess the severity of bleeding, the classification of the Committee of the International Society on Thrombosis and Haemostasis (ISTH) was used.Results In patients without prophylactic compression (Group 1) there were 7 VTEC cases (10.14%); deep vein thrombosis (DVT) — 4 (5.8%), pulmonary embolism (PE) — 3 (4.3%). All 6 cases (8.7%) with PE were fatal. It was noted that 2 cases of PE (2.8%) were verified upon autopsy, and not clinically. In patients of the 2nd group with the use of elastic compression, the overall incidence of VTEC was only one case (1.6%). When analyzing the frequency of bleeding in the 1st group, there was one pulmonary bleeding (1.4%), in the 2nd group there was also one case of intense intermuscular hematoma (1.6%). Significant bleeding was observed in one patient (1.4%) of the 1st group, and in 3 (4.8%) cases of the 2nd group. The minor bleeding was observed in 11 patients (15.9%) of the 1st group, and in 8 (12.7%) patients of the 2nd group. The mortality during hospitalization was 11 (15.9%) cases in patients of the 1st group (without EC) and 7 (11.1%) in patients of the 2nd group (with EC) (p=0.419).Conclusions The mortality in patients with coronavirus infection without compression therapy is higher than in patients with compression stockings (p=0.419). Patients wearing compression stockings in the hospital had a low incidence of VTEC (1.6% of cases in group 2 versus 10.14% of cases in group 1, p=0.039). The study groups had the same frequency of bleeding (group 1 — one case (1.4%), group 2 — one case (1.6%). The use of preventive compression at the inpatient stage of treatment of a new coronavirus infection makes it possible to prevent VTEC in patients with bleeding when anticoagulant therapy is not possible.